Sound recording technologies influence on creation and translation of musical pieces - A. M. Tormakhova, (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of the influence of technology evolution on the process of producing and replicating works of art. There is a transformation of musical creativity, which occurs due to the opportunities that arise because of sound recording technologies development, processing and reproduction of musical sound. The process of performing a musical pieces and actually creating it are experiencing great improvisation. Live looping enables recording and playing looped audio samples in real time using special devices or software. The ability to create audio tracks and to use them in "real time" can concern both the concert activity of leading and well-known musicians, recordings in professional studios of performers of different genre and style directions, but the most expedient and influential are those who create compositions in "amateur" single. This expediency is based on the spectrum of practical application of one's own voice, which is impossible without devices equipped with such a technology. The development of artistic practice is not possible beyond the cultural context. Changes in one of the cultural spheres associated with emergence of ability to record audio, emergence of new technologies, software – necessarily lead to essential or structural modifications in other areas. Using the principle of live looping allows you bypass most of the links associated with the show business infrastructure. However, the essence and stages of creative process remain largely unchanged. Improvisation, which is proclaimed as the main form of presentation of musical material while using live looping, becomes a pledge of creative maturity and skill of the performer, who acts as a composer, arranger and sometimes even a conductor. The development of the technological level helps create artistic projects, the appearance and implementation of which will depend on one person.
Keywords: sound recording, voice, live looping, listener, performer, technology